Medical Expulsive Therapy for Distal Ureteral Stones: Tamsulosin Versus Silodosin in the Turkish Population - AKDENİZ, ESRA (CUREUS INC, 2017)
Introduction Our aim was to contribute a study that includes a higher patient population to the limited number of studies comparing tamsulosin and silodosin in the treatment of distal ureteral stones. Material and methods Patients who presented with renal colic to the urology emergency clinic and were diagnosed with ureteral stones and followed-up with conservative treatment between January 2010 and January 2016 were retrospectively screened. According to the inclusion-exclusion criteria, the patients were divided into three groups. Group 1: 150 patients followed with watchful waiting (WW), Group 2: 156 patients who received 0.4 mg of tamsulosin daily, and Group 3: 159 patients who received 8 mg of silodosin daily. The side effects of the used drugs, duration of stone reduction, and expulsion rates were evaluated and compared separately. Results A total of 465 patients were included in the study. No statistically significant difference was found in terms of age, gender, and stone size among the groups. The patient characteristics and results are shown in Table 1. The differences in stone expulsion rate between the groups in the first week were calculated using the Chi-square test and found to be non-significant (p = 0.155); whereas, the stone expulsion rates between Group 1 versus Group 2 and Group 1 versus Group 3 were found to be significantly different after the second and third week. Conclusion According to our results, no statistically significant superiority between tamsulosin and silodosin was shown in the treatment of distal ureteral stones in the Turkish population.
Keywords: tamsulosin; silodosin; ureter; stone; EFFICACY; MANAGEMENT; FACILITATE; PASSAGE